Recent advances in the electrochemical synthesis of organophosphorus compounds - Kaboudin, Babak; Behroozi, Milad; Sadighi, Sepideh; Asgharzadeh, Fatemeh (Beilstein Journal of Organic Chemistry, 2025)
In this review, we describe recent advances in electrochemical green methods for the synthesis of various organophosphorus compounds through the formation of phosphorus–carbon, phosphorus–nitrogen, phosphorus–oxygen, phosphorus–sulfur, and phosphorus–selenium bonds. The impact of different electrodes is also discussed in this matter. Graphite, platinum, RVC, and nickel electrodes have been used extensively for the electrochemical synthesis of organophosphorus compounds. The recent advances in the electrochemical synthesis of organophosphorus compounds have made this method a promising method for preparing various structures. This review is an introduction to encourage scientists to use electrosynthesis as a green, precise, and low-cost method to prepare phosphorous structures.
Keywords: electrosynthesis; green synthesis; organophosphorus compounds; P–C bond formation; P–heteroatom bond formation